THE DROWNING POLICY THE FOREIGN FISHING VESSELS OF ILLEGAL FISHINGBY INDONESIA GOVERNMENT IN INTERNATIONAL LAW PERSPECTIVE - Amry Mangihut Tua (Legal Standing : Jurnal Ilmu Hukum, 2019)
The drowning of foreign fishing vessels of illegal fishing actors in Indonesia teritory is one of law enforcement efforts to against the eradication of illegal fishing and to enforce the sovereignty of the territory of the Republic of Indonesia. It is a special act mandated in Article 69 paragraph (4) of Law No. 45 of 2009 on fisheries. This sinking policy invites controversy from neighboring countries because it is considered as an action that violates the principle of peaceful dispute resolution and is not regulated in international law. Indonesia keep continues to enforce this policy because it is considered the most effective step in reducing massive illegal fishing in Indonesian waters and has a deterrent effect for the actors. Keywords: drowning policy of foreign ship, illegal fishing, international law